The misanthrope - Wilbur, Richard (London : Faber and faber Ltd., 1966)
Lyceum Theatre, APA-Phoenix (a project of Theatre Incorporated) presents the APA Repertory Company, "The Misanthrope," by Moliere, English version by Richard Wilbur, directed by Stephen Porter, scenery and lighting by James Tilton, costumes designed by Nancy Potts, music by Conrad Susa, stage managers Nikos Kafkalis, Harley Hackett, Chet Leaming.
Lyceum Theatre, January 1969.
APA repertory company, Ellis Rabb, artistic director, Norman Kean, general manager. Cast: Brian Bedford, Joseph Bird, Barry Bostwick, Alan Brasington, Martha Bundy, Alexander Clark, Peter Coffield, Patricia Conolly, Clayton Corzatte, Keene Curtis, Jake Dengel, Michael Durrell, Richard Easton, Alan Fudge, Gordon Gould, James Greene, Suzanne Grossmann, Harley Hackett, Jennifer Harmon, Brooke Harrow, Helen Hayes, Katherine Helmond, Chet Leaming, Amy Levitt, Betty Miller, Philip Minor, Donald Moffat, Etain O'Malley, George Pentecost, Christine Pickles, Ellis Rabb, Drew Snyder, Frances Sternhagen, Nancy Walker, Sydney Walker, Ralph Williams, Richard Woods.
Title devised by Library staff.
LC copy shelved under: Cock-a-doodle dandy. Accompanied by playbill for APA-Phoenix 1968-69 season, and addition to program of "Cock-A-Doodle Dandy."
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: Molière -- 1622-1673 -- Translations into English